Synthesis and thermoresponsive solution properties of poly[oligo(ethylene glycol) (meth)acrylamide]s: Biocompatible PEG analogues - Chua, G.; Roth, P.; Duong, H.; Davis, T.; Lowe, Andrew (2012)
A library of (meth)acrylamido (co)polymers was prepared by reacting poly(pentafluorophenyl (meth)acrylate) with α-amino, ω-methoxy functionalized di(ethylene glycol), tri(ethylene glycol), and poly(ethylene glycol) (PEG)-350, PEG-750, and PEG-5k, in combination with hexylamine or thyroxine. The resulting copolymers showed an improved solubility in water (higher or absent LCST values) and in alcohols (lower or absent UCST values) than the analogous common series of poly[oligo(ethylene glycol) methyl ether (meth)acrylates]. The polyacrylamido species showed a better solubility than the corresponding polymethacrylamido derivatives of similar molecular weight with all polyacrylamides investigated being water-soluble at temperatures exceeding 90.0 °C. Tunable thermosensitive behavior could be effected by the incorporation of the hydrophobic hexylamide comonomer. Similarly, an acrylamido backbone with grafted oligo(propylene glycol 600) amides exhibited a sharp LCST-type transition around 22.0 °C. The UCST-type transitions of the (meth)acrylamido homopolymers were evaluated in 2-propanol and 1-octanol and were found to increase with an increasing ethylene glycol side chain length, but were essentially independent of the alcohol chain length with polymers exhibiting higher UCST transitions in 2-propanol vs 1-octanol.Cytotoxicity tests on MRC5 fibroblast cells of the di- and tri(ethylene glycol) methyl ether acrylamido homopolymers revealed no toxicity up to concentrations of 10.0 g/L. By employing mixtures of di(ethylene glycol) methyl ether amine and the prohormone thyroxine (T4), water-soluble copolymers containing varying amounts of T4 could be easily synthesized. Because of enhanced solubility, low toxicity, and higher hydrolytic stability of amides versus ester linkages, activated ester polymers in combination with amino-functionalized ethylene glycol based side chains are presented as a versatile platform for highly soluble, biocompatible, bioconjugated materials.